Paradigma Pembangunan Desa dalam Pengelolaan Keuangan Desa Berdasarkan Undang-Undang Nomor 6 Tahun 2014 Tentang Desa - Betha Rahmasari (Volksgeist: Jurnal Ilmu Hukum dan Konstitusi, 2020)
This article aims to find out the developmentidea or paradigm through village financial management based on Law Number 6 of 2014 concerning Villages. In this study, the researcher used a normative research methodby examining the village regulations in depth. Primary legal materials are authoritatuve legal materials in the form of laws and regulations. Village dependence is the most obvious violence against village income or financial sources. Various financial assistance from the government has made the village dependent on financial sources from the government. The use of regional development funds is intended to support activities in the management of Regional Development organizations. Therefore, development funds should be managed properly and smoothly, as well as can be used effectively to increase the people economy in the regions. This research shows that the law was made to regulate and support the development of local economic potential as well as the sustainable use of natural resources and the environment, and that the village community has the right to obtain information and monitor the planning and implementation of village development.